A visible-light-responsive TaON/CdS photocatalytic film with a ZnS passivation layer for highly extraordinary NO2 photodegradation. Issue 54 (3rd September 2020) - Yan, Dandan; Wei, Tingting; Fang, Wencheng; Jin, Zhanbin; Li, Fengyan; Xia, Zhinan; Xu, Lin
Abstract : The TaON/CdS/ZnS film displayed a highly efficient NO2 photodegradation rate under visible light irradiation and possessed remarkable recyclability for NO2 degradation. Abstract : Recently, TaON has become a promising photoelectrode material in the photocatalytic field owing to its suitable band gap and superior charge carrier transfer ability. In this work, we prepared a TaON/CdS photocatalytic film using a CdS nanoparticle-modified TaON film by the successive ionic layer adsorption and reaction (SILAR) method. For the first time, the ZnS nanoparticles were deposited on the TaON/CdS film using the same method. We found that pure TaON had a nanoporous morphology, thus resulting in high specific surface area and better gas adsorption capacity. Furthermore, the TaON/CdS/ZnS film displayed a highly efficient NO2 photodegradation rate under visible light irradiation owing to its stronger visible light response, photocorrosion preventive capacity, and the high separation efficiency of photo-induced electrons and holes. Interestingly, the promising TaON/CdS/ZnS film also possessed remarkable recyclability for NO2 degradation. Therefore, we suggest that the TaON/CdS/ZnS photocatalytic film might be used for the photocatalytic degradation of other pollutants or in other applications. We also put forward the feasible NO2 photocatalytic degradation mechanism for the TaON/CdS/ZnS film. From the schematic diagram, we could further obtain the photo-generated carrier transport process and NO2 photodegradation principle in detail over the ternary photocatalytic film. Moreover, the trapping experiment demonstrates that ·O2 − and h + all play significant roles in NO2 degradation under visible light irradiation.